Bio-Assisted Synthesis of Food-Grade FeOOH Nanoellipsoids as Promising Iron Supplements for Food Fortification - Karami-Darehnaranji, Mahboubeh; Taghizadeh, Seyedeh-Masoumeh; Mirzaei, Esmaeil; Heidari, Reza; Berenjian, Aydin; Ebrahiminezhad, Alireza (Applied Food Biotechnology, 2020)
Background and Objective: Nanostructures of FeOOH are approved substitutions for iron salts in treatment of iron deficiencies. These particles can be promising additives to develop iron fortified foods. Researchers are interested to develop cost-effective techniques for the fabrication of food-grade FeOOH nanostructures. Relatively, polyethylenimine is commonly used to fabricate FeOOH nanoellipsoids. However, food industries need to develop novel protocols, which can be used in food processing. In this study, a simple economic technique was developed for the fabrication of food-grade FeOOH nanoellipsoids. Material and Methods: Ferric chloride hexahydrate (FeCl3.6H2O) was used as iron precursor. BG-11 broth medium was used to cultivate Chlorella vulgaris microalgae. The Chlorella vulgaris culture supernatant was used for the fabrication of FeOOH nanostructures as an approved low-cost medium by the Food and Drug Administration. Nanoellipsoids of FeOOH were synthesized via hydrolysis of ferric ions in culture supernatants with no addition of other chemicals. Results and Conclusion: Results showed that the prepared nanoellipsoids were β-FeOOH with 51.4-nm average length and 9.2-nm average width. The XRD analysis demonstrated that the secretory compound from Chlorella vulgaris included no negative effects on formation of FeOOH nanocrystals. The current developed technique can be introduced as a promising approach in fabrication of food-grade nanoparticles. Furthermore, the prepared structures can be used for the supplement formulation in pharmaceutical industries. Conflict of interest: The authors declare no conflict of interest.